Regioselective synthesis of novel 5-nitro-naphthoquinone derivatives: Electrochemistry and in-situ spectroelectrochemistry properties - UĞUZ NELİ, ÖZLEM; KOCA, ATIF (My University, 2022)
The novel N-,O-substituted-5-Nitro-1,4-naphthoquinones (NQ) as regioisomers were synthesized by reactions of 2,3-dichloro-5-nitro-1,4-naphthoquinone with some heterocyclic rings which were substituted with various nucleophiles according to a Michael 1,4-addition mechanism. All synthesized compounds were characterized by elemental analysis, electrospray ionization mass spectrometry (ESI-MS), Fourier transform infrared spectroscopy (FT-IR), H-1-nuclear magnetic resonance (H-1 NMR) and attached proton test nuclear magnetic resonance (APTNMR). Two-dimensional techniques H-1-H-1 correlated spectroscopy (COSY) was used for characterization of compound 1a. Cyclic and square wave voltammetric and in situ UV-Vis spectroelectrochemical characterizations of NQ derivatives were carried out to determine redox mechanism of these molecules. Although in-situ FT-IR spectroelectrochemical studies of these type compounds were frequently reported in the literature, this is the first study for the in-situ UV-Vis spectroelectrochemical studies of NQ compounds in the literature. All NQs illustrated two NQ based and one nitro-based reduction reactions. While NQ based reduction couples were electrochemically and chemically reversible, observation of nitro reduction at more negative potentials made all processes irreversible. Altering the substituents of the NQ derivatives slightly influenced the redox potentials and chemical reversibility of the processes. Isomers of different NQ derivatives almost showed similar voltametric responses. Distinct spectral and color changes were observed during the redox reactions which indicated possible usages of these molecules in display technologies.
Keywords: Kimya; Fizikokimya; Temel Bilimler; Chemistry; Physical Chemistry; Natural Sciences; KİMYA, FİZİKSEL; Temel Bilimler (SCI); CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); Yüzeyler ve Arayüzler; Kimya (çeşitli); Genel Kimya; Fiziksel ve Teorik Kimya; Yüzeyler, Kaplamalar ve Filmler; Fizik Bilimleri; Surfaces and Interfaces; Chemistry (miscellaneous); General Chemistry; Physical and Theoretical Chemistry; Surfaces, Coatings and Films; Physical Sciences; Quinone; 5-Nitro-1,4-naphthoquinone; Regioisomer; Cyclic Voltammetry; In situ UV -Vis spectroelectrochemistry; REDUCTION; VITRO; 1,4-NAPHTHOQUINONE; NAPHTHOQUINONES; ANTIOXIDANT; COMPLEXES